Co‐Assembled Cellulose Nanocrystal‐Based Materials with Enhanced Long‐Term Stabilization in the Air of Black Phosphorus Nanosheets via Integrating Physical Coverage with Chemical Interactions. Issue 6 (28th October 2021) - He, Yi; Liu, Siyuan; zhou, Na; Ahmad, Ishak; Gan, Lin; Huang, Jin
Abstract: Black phosphorus nanosheets (BPNS) cannot be directly applied in moist air due to their chemical instability from their thin layer structures adsorbed and transferred oxygen atoms easily. Here, a universal strategy for stabilizing BPNS is proposed by exfoliating black phosphorus with one‐dimensional nanoparticles based on cellulose nanocrystals (CNCs). Thin layers of BPNS are obtained in water and then co‐assembled with CNCs to construct composite membranes. Meanwhile, the co‐assembling technology and the chemical structure of CNCs are adjusted to obtain flexible membranes and high photothermal energy‐conversion efficiency (19.6%). The infrared illumination test proves that BPNS can exist stably in the black phosphorus (BP)/CNC‐based membranes and the photothermal conversion efficiency is kept at 19.6% after 30 days in ambient air. The mechanism study based on atomic force microscopy (AFM) and XPS show that the stability comes from the effects of physical covering and chemical covalent‐bond stabilization of CNC‐based materials. These BP/CNC‐based co‐assembled membranes can be practically applied in the military field for infrared ignition, night vision, and photothermal sensing. Abstract : Co‐assembly black phosphorus nanosheets with CNC‐based materials for long‐term stabilization in the air via both physical covering and chemical modification.